The limit drawing ratio in die angled hydromechanical deep drawing method - Ballikaya, Hasan; Savas, Vedat; Ozay, Cetin (Springer London Ltd, 2020)
In the study, the effect of die angle, die radius, die punch, blank holder force, and chamber pressure parameters on the limit drawing ratio (LDR) in die angled hydromechanical deep drawing process was investigated by using Taguchi experimental design method. The effects of the parameters on the limit drawing ratio were numerically examined and compared experimentally using ANSYS packaged software. Also, the data were statistically analyzed by using the ANOVA analysis of variance in order to determine the effects of the parameters on the limit drawing ratio. The results indicated that the chamber pressure value was lower and the limit drawing ratio was higher than the values reported in the literature.
Keywords: Die angled hydromechanical deep drawing; Taguchi; Anova; ANSYS